Forest Fire Disaster Mitigation Through Social Policy Implementation in Peat Ecosystem Management - Anton Budi Dharma; Sujianto Sujianto; Yustina Yustina; Febri Yuliani (UIN Sunan Gunung Djati, 2024)
Forest fires are a problem that often hit Riau Province. Therefore, there is a need for mitigation efforts to deal with this forest fire disaster. One of the steps that can be taken is by implementing peat ecosystems. This research then aims to see how the implementation of peat ecosystems can mitigate forest fires, especially in Riau Province. This research will be conducted using a descriptive qualitative approach. The data used in this research comes from various previous research results that are still relevant to this research. The results of this study found that in implementing peat ecosystems, there are still challenges that need to be faced, such as climate change and land use. To overcome this, various opportunities such as technological developments and stakeholder collaboration can be implemented. In mitigating forest fires, conservation and restoration of peat ecosystems are important steps to strengthen the resilience of the ecosystem.